PENEGAKAN HUKUM TERHADAP TINDAK PIDANA MEMPERJUALBELIKAN DRIVE GOOGLE BERISI KONTEN PORNOGRAFI - Rizky Willy Kurniawan (2023)
The convenience of Google Drive can be misused by irresponsible people. One form of this abuse is by uploading pornographic content to Google Drive and then the Google Drive will be sold by the uploader to anyone who will buy it, as was done by Dea Onlyfans who sold it to Marshel Widianto. Misuse of Google Drive by trading Google Drive containing pornographic content raises a question whether trading Google Drive containing pornographic content is permissible or not and how to eradicate the trading of Google Drive containing pornographic content. on the questions that arise using normative juridical research methods can draw the conclusion that there are legal arrangements related to the crime of trading google drives containing pornographic content and efforts to eradicate buying and selling of google drives containing pornographic content